DEVELOPMENT OF PRESENTATION MEDIA BASED ON PREZI IN FUNGI SUBJECT FOR GRADE X - Liya Indrawati; Endang Susantini; Ulfi Faizah (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2019)
Fungi is a very broad topic. Because of this breadth, learning media are needed so it can help students to understand allfungi subject. The media needed can at least attract students' interest in studying fungi subject. One of suitable medium isPrezi-based presentation media that can display audio and visuals in delivering material and also can be zoomed in andzoomed out . This study aims to produce a Prezi-Based Presentation Media at fungi subject in grade X high school anddescribe its validity. Media development is done at Biology Department, Faculty of Mathematics ans Natural Sciences,Universitas Negeri Surabaya by using (ASSURE) Analyze Learner, State Objective, Select Media and Materials, UtilizeMedia and Materials, Require Learner Participation, Evaluate and Revise method. The media validity assessment sheetrefers to the Likert scale. The media is reviewed by writing down whether there are any aspects expected in eachcomponent and assessed with a range of scores from 1 to 4, with the category score 1 : less decent, 2 : quite decent, 3 :decent and 4 : very decent. The media was validated by two biology lecturers. Based on the results obtained, Prezi-basedpresentation media is declared decent with an average value of 3.28 and should be tested in terms of its validity.Keywords: Multimedia, Prezi, Fungi subject.